Tumor markers in clinical oncology - Novaković, Srdjan (Radiology and oncology (Ljubljana), 2004)
The subtle differences between normal and tumor cells are exploited in the detection and treatment of cancer. These differences are designated as tumor markers and can be either qualitative or quantitative in their nature. That means that both the structures that are produced by tumor cells as well as thestructures that are produced in excessive amounts by host tissues under theinfluence of tumor cells can function as tumor markers. Speaking in general, the tumor markers are the specific molecules appearing in the blood or tissues and the occurrence of which is associated with cancer. According totheir application, tumor markers can be roughly divided as markers in clinical oncology and markers in pathology. In this review, only tumor markersin clinical oncology are going to be discussed. Current tumor markers in clinical oncology include (i) oncofetal antigens, (ii) placental proteins, (iii) hormones, (iv) enzymes, (v) tumor-associated antigens, (vi) special serum proteins, (vii) catecholamine metabolites, and (viii) miscellaneous markers. As to the literature, an ideal tumor marker should fulfil certain criteria - when using it as a test for detection of cancer disease: (1) posirive results should occur in the early stages of the disease, (2) positiveresults should occur only in the patients with a specific type of malignancy, (3) positive results should occur in all patients with the same malignancy, (4) the measured values should correlate with the stage of the disease, (5) the measured values should correlate to the response to treatment, (6) the marker should be easy to measure. Most tumor markers available today meet several, but not all criteria. As a consequence of that, some criteria were chosen for the validation and proper selection of the most appropriate marker in a particular malignancy, and these are: (1) markers' sensitivity, (2) specificity, and (3) predictive values. (Abstract truncated at 2000 characters).
Keywords: Alfa-fetoproteini; Alpha-Fetoproteins; Antigeni, tumor-povezani, ogljikohidratni; Antigens, Tumor-Associated, Carbohydrate; Carcinoembryonic Antigen; Diagnosis; diagnostika; Karcinoembrionalni antigen; Neoplasms; Novotvorbe; Občutljivost in specifičnost; onkologija; Sensitivity And Specificity; tumor; Tumor Markers, Biological; tumorski označevalci; Tumorski označevalci biološki